Psychological characteristics associated with ultra‐marathon running: An exploratory self‐report and psychophysiological study. (18th March 2020) - Roebuck, Gregory S.; Urquhart, Donna M.; Che, Xianwei; Knox, Laura; Fitzgerald, Paul B.; Cicuttini, Flavia M.; Lee, Stuart; Segrave, Rebecca; Fitzgibbon, Bernadette M.
Abstract: Objective: Ultra‐marathon running is an extremely demanding sport. Psychological factors that affect responses to stressors and may contribute to ultra‐runners' ability to engage in their sport include resilience, personality characteristics, and affective processing. This exploratory study investigated ultra‐runners' resilience, personality traits, emotion regulation abilities, and self‐report and physiological responses to emotionally negative stimuli. Method: Twenty ultra‐runners and 20 non‐running controls completed the Connor–Davidson Resilience Scale (CD‐RISC), Emotion Regulation Questionnaire, Cognitive Emotion Regulation Questionnaire (CERQ), and Multidimensional Personality Questionnaire–Brief Form (MPQ–BF). Participants also completed a computerised emotion regulation task in which they were instructed to down‐regulate their responses to emotionally negative images. They provided self‐report ratings of their responses to the images and their heart rate and skin conductance responses were also recorded. Results: The ultra‐runners scored higher than controls on the CD‐RISC ( p = .014; d = 0.81) and Positive Reappraisal subscale of the CERQ ( p = .034; d = 0.70). They also scored lower on the Social Closeness scale of the MPQ‐BF ( p = .037; d = −0.68). In the emotion regulation task, they did not differ in their self‐report responses to negative images but displayed smaller cardiac and skin conductance responses to these images (both p = .04; η p 2  ≥ .11). Conclusions: Compared with non‐runners, ultra‐runners appear to be more resilient, more likely to engage in positive reappraisal, lower in affiliative extraversion, and less physiologically responsive to emotionally negative stimuli. They otherwise appear to be broadly similar to non‐runners with respect to their personality traits and emotion regulation processes.